Study on polyester composite nanofiltration (nf) membrane by interfacial polymerization for Natural Organic Matter (NOM) removal - Nurul Suhada, Drahim (2013)
The polyester composite nanofiltration (NF) membrane has been prepared by interfacial polymerization for natural organic matter (NOM) removal. The effect of reaction time on the production of thin film composite NF and it affect on the NOM and Sodium Chloride (NaCl) removal performance was conducted. The thin film composite membranes were synthesized through interfacial polymerization with monomer concentration of 2% w/v of triethanolamine (TEOA) and then react with organic solution of trimesoylchloride (TMC) at different reaction time to produce a new layer polyester on top of polyethersulfone (PES) miroporous support. The fabricated thin film composite membranes were characterized in term of water flux and permeability. It was found that the Polyester NF membrane with different reaction time (15, 25 and 35 minute) which prepared through interfacial polymerization can reduce the humic acid concentration. Besides that, the variation of reaction time in interfacial polymerization technique improved the filtration performance of the membrane. The result shows that the flux and permeability were decreased as the reaction time increased while opposite trend for NOM and NaCl rejections were observed.